2008
DOI: 10.1007/s11999-008-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Inlay Failure in Cemented Polyethylene-backed Total Hip Arthroplasty

Abstract: Alumina-on-alumina bearings for THA have markedly improved in mechanical properties through advances in technology; however, alumina fracture is still a concern. We retrospectively reviewed 77 patients (82 hips) with cemented alumina-on-alumina THAs to identify factors relating to alumina failure. The mean age of the patients at surgery was 63 years. The prostheses had a cemented polyethylene-backed acetabular component with an alumina inlay and a 28-mm alumina head. Revision surgery was performed because of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
(51 reference statements)
0
13
1
Order By: Relevance
“…During the past decade, various studies have reported outcomes and survival of alternative bearing surfaces in THA [6,7,9,12,14,15,19,20,[23][24][25]. Complications associated with the use of hard-on-hard bearings include squeaking, fracture, liner disassociation, metallosis, and hypersensitivity reactions occurring in some patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, various studies have reported outcomes and survival of alternative bearing surfaces in THA [6,7,9,12,14,15,19,20,[23][24][25]. Complications associated with the use of hard-on-hard bearings include squeaking, fracture, liner disassociation, metallosis, and hypersensitivity reactions occurring in some patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Hasegawa et al [11] reviewed 35 consecutive hips with a layered component at six years and reported two liner fractures (5.7%). Iwakiri et al [27] reported a fracture rate of 5.6% (4/82) at eight years associated with periacetabular radiolucent lines (cemented cup) and could determine three causes: small ceramic thickness (four mm), small alumina clearance (five to 35 μm) and small oscillation angle (<120°). Park et al [15] reported a 1.1% (4/357) fracture rate of the sandwich liner at three year follow-up in a multicentre study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent retrospective study, Petsatodis et al reported a survivorship of 84.4% of cementless alumina COC prostheses at 20 years follow-up 23 . Others have reported significant differences in survivorship of COC bearings depending on the type of prosthesis and its fixation, especially with respect to cementless and cemented cups [24][25] . Therefore, the survivorship and rate of complications of ceramic bearing surfaces depend not only on the period of implantation (and therefore the generation of ceramic material), but also on other important factors e.g.…”
Section: Clinical Evidence For Ceramic-on-ceramic Thamentioning
confidence: 99%